The art of solidarity : visual and performative politics in Cold War Latin America - Stites Mor, Jessica; Suescun Pozas, Maria del Carmen (University of Texas Press, 2018)
The Cold War claimed many lives and inflicted tremendous psychological pain throughout the Americas. The extreme polarization that resulted from pitting capitalism against communism held most of the creative and productive energy of the twentieth century captive. Many artists responded to Cold War struggles by engaging in activist art practice, using creative expression to mobilize social change. The Art of Solidarity examines how these creative practices in the arts and culture contributed to transnational solidarity campaigns that connected people across the Americas from the early twentieth century through the Cold War and its immediate aftermath. This collection of original essays is divided into four chronological sections: cultural and artistic production in the pre?Cold War era that set the stage for transnational solidarity organizing; early artistic responses to the rise of Cold War polarization and state repression; the centrality of cultural and artistic production in social movements of solidarity; and solidarity activism beyond movements. Essay topics range widely across regions and social groups, from the work of lesbian activists in Mexico City in the late 1970s and 1980s, to the exchanges and transmissions of folk-music practices from Cuba to the United States, to the uses of Chilean arpilleras to oppose and protest the military dictatorship. While previous studies have focused on politically engaged artists or examined how artist communities have created solidarity movements, this book is one of the first to merge both perspectives.